CHINESE INITIATIVE «ECONOMIC BELT OF THE GREAT SILK ROAD» AND THE PROBLEM OF ENERGY SECURITY IN EURASIA - A. M. Mastepanov (Проблемы постсоветского пространства)
Ensuring global energy security is one of the major systemic challenges facing the global energy sector. The article shows the role of Eurasia in the modern world, analyzes the peculiarities of understanding and interpretation of energy security challenges in its major regions and groups of countries. Shows the role of Russian-Chinese strategic partnership, the problems of implementation of three major projects on the continent - the Eurasian economic Union, Shanghai cooperation organization and the Chinese land of the project "Economic belt of the Great silk road" and their possible impact on energy security as Russia and China and all of Eurasia. Justified the principle of reasonable sufficiency diversification of energy supplies and energy markets.